Power and Political Communication. Feasting and Gift Giving in Medieval Iceland - Palsson, Vidar (eScholarship, University of California, 2010)
The present study has a double primary aim. Firstly, it seeks to analyze the sociopolitical functionality of feasting and gift giving as modes of political communication in later twelfth- and thirteenth-century Iceland, primarily but not exclusively through its secular prose narratives. Secondly, it aims to place that functionality within the larger framework of the power and politics that shape its applications and perception.